Barangay Officials’ Manifestation of Basic Functions in Addressing Public Safety and Security Threats - Maranan, Mildred (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the correlation between Barangay Officials' level of manifestation of basic deliverables within the framework of the Local Government Code of 1991 and the seriousness of public safety and security threats. Utilizing a quantitative descriptive correlational design, data were collected from 401 regular residents and Barangay Officials. Results indicate that Barangay Halang officials perform strongly in executive, legislative, and judiciary functions, with mean scores of 3.65, 3.68, and 3.68, respectively, classified as "Fully Manifested." A significant discrepancy was observed between resident and official assessments, evidenced by a T-test value of 3.42 and a p-value of less than .001, with officials rating their performance higher. Public safety and security threats were rated "Very Serious" in areas such as health and social welfare services, hygiene and sanitation, beautification, solid waste collection, "katarungang pambarangay," and infrastructure facilities, with mean values ranging from 3.60 to 3.75. Additionally, significant moderately small positive correlations (p < 0.001) were identified between the officials' performance in basic deliverables and the perceived seriousness of public safety threats. The study concludes that while Barangay Halang officials perform strongly, there are opportunities for improvement, especially in stakeholder collaboration and addressing diverse community needs.